Akeptabilitas Panduan Bimbingan Kelompok Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMK - Kurniawan, Nanda Alfan; Hidayah, Nur; Rahman, Diniy Hidayatur (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
Group guidance is one of the guidance and counseling service settings carried out by counselors for vocational high school students. Group guidance is a form of service provided by counselors to counselees / students to make decisions by utilizing group dynamics. The group dynamics that occur during the guidance will encourage each member to interact. Socrates dialogue is a dialogue technique in depth to examine the thoughts that arise from the information provided in a process of interaction. This study aims to describe the acceptability of the Socrates dialogue technique group guidance guide within the framework of a problem-based learning model to improve the critical thinking skills of vocational school students. Guidance analysis technique used Aiken rater analysis with tests by two counseling and guidance experts. The results of the analysis based on expert testing obtained the clarity aspect validity index of 0.83 (high) and the accuracy aspect validity index of 0.83 (high). Based on the test results, it can be concluded that the guidelines have met the acceptance criteria for the aspects of clarity and accuracy to be used as a group guidance guide for vocational students.